Penafsiran Volume Pohon Pinus merkusii melalui Foto Udara (Studi Kasus BKPH Majenang, KPH Banyumas Barat) - Sahid Sahid (Fakultas Kehutanan Universitas Gadjah Mada, 2010)
Interpretation of Stock Volume of Pinus merkusii using Aerial Photographs (Case Study in BKPH Majenang, West Banyumas FMUThe study aims to compile and analyse the growing stock volume of Pinus merkusii by using stand parameter measured through aerial photographs. The study was conducted by using black-white panchromatic aerial photographs produced in 2005 and the scale was 1 : 20,000. The study was conducted in Pinus merkusii taping plots in the Majenang BKPH, under the forest districts of west Banyumas, Perum Perhutani using tree height, crown diameter and number of trees per hectare as parameters. Data analysis was done to define the relationship among these parameters in regression equation. The steps of the study were defining measurement plots in aerial photographs, measurement of stand parameters in the aerial photographs and field observation. Data analysis was performed using micro computer. As a result, the regression equation for each location as follows: V = 72,415 – 0,231 N + 35,242 H – 24,454D – 0,923 (N x D), with the determination coefficient was 0,789 and the significance of 95%. Where: V = growing stock volume (m3), N = the number of trees per hectare, H = tree height (m) and D = crown diameter (m). It was concluded that number of tree per hectare, tree height and crown diameter were good predictors for standing stock volume of Pinus merkusii.